Analysis of Students’ Perception toward Online Biology Learning using e-learning Madrasah at Islamic Senior High School (MAN) Penajam Paser Utara - Nigmah, Choirun; Masitah, Masitah; Purwati, Sri; Jailani, Jailani (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
Online learning is extremely common during the Covid-19 pandemic. That sudden alteration, from offline to online learning affect the learning process including the perception of students and teachers using online learning platform. The aims of this study are to determine the students’ perceptions of class XI MIA on online biology learning by using Madrasah E-Learning at MAN Penajam Paser Utara. The data was collected by conducting the observations, interviews and questionnaires. The questionnaire was in Likert scale form that has been valid and reliable (ralpha= 0, 836) with a very strong category. The indicators that were studied include the indicators of student activity, indicators of student perceptions of Madrasah E-Learning and the indicators of factors that affect learning in network (online). Descriptive statistical techniques were the data analysis technique that was used in the form of descriptive, frequency distribution and percentage. The results showed that the activity based on the attendance and collection of student assignments during online biology learning was in the good category. Students' perceptions of Madrasah E-Learning are in very positive category with 63.89%. However, the use of Madrasah E-Learning is still not effective due to network constraints and the lack of teacher skills and knowledge regarding the use of Madrasah E-Learning features. The factors that influence learning in the network include learning support facilities such as cellphones and laptops, network factors and internet quotas, motivational factors, learning interest factors, family factors, home atmosphere factors, environmental factors, and economic factors